Correlation between hemoglobin level and left ventricular systolic functions and dimensions in children with chronic severe anemia - Erlina Masniari Napitupulu; Fera Wahyuni; Tina Christina L. Tobing; Muhammad Ali; Bidasari Lubis (Paediatrica Indonesiana, 2011)
Background Chronic severe anemia is a connnon disease. Cardiac output may increase when the hemoglobin (Hb) level decreases to < 7 g/dL for 3 months or more. Alteration of left ventricular (LV) function occurs frequently in children 'With chronic severe anemia, in the {onn of concentric LV hypertrophy, LV dilatation with or v.ithout LV hypertrophy, or systolic dysfunction. Objective To examine the correlation between Hb level and alteration of LV systolic function in children with chronic severe anemia. Methods We conducted a cross-sectional study in Adam Malik Hospital from October to December 2009. Subjects were chronic severely anemic children. Left ventricular systolic function (ejection fraction/EF, fractional shortening/FS) and dimensions (left ventricular end diastolic diameter/LVEDD and left ventricular end systolic diameter/LVESD) were measured using Hitachi EUB 5500 echocardiography unit. Univariate analysis  and Pearson correlation were performed.Results Thirty children were enrolled in the study. The mean of age was 113.5 months (SD 53.24). Hb values ranged from 2.1 to 6.9 g/dL with mean value of 4.6 g/dL (SD 1.44). Mean duration of anemia was 3.9 months (SD 0.70). Chronic severe anemia was not associated \\lith decreased LV systolic function [EF 62.2% (SD 9.16), r =0.296, P=0.112; FS 33.8% (SD 7.26), r =0.115, P=0.545], nor LV dimension changes [LVEDD 40.2 mm (SD 6.85), r = -0.192, P=0.308; LVESD 26.2 mm (SD 4.98), r=-0.266, P=0.156]. Conclusion There was no correlation between Hb level in chronically anemic children and changes in LV systolic function or dimension.